2018
DOI: 10.3989/gya.0109181
|View full text |Cite
|
Sign up to set email alerts
|

Influences of genotype and location interactions on oil, fatty acids and agronomical properties of groundnuts

Abstract: An enhanced adaptation to specific environmental conditions could provide higher seed quality and quantity from groundnuts. In this investigation, nine groundnut genotypes and two controls were evaluated for morphological and oil traits in two different Mediterranean locations. The traits of shelling percentage and pod yield indicated significant differences among the genotypes. The highest pod yield was observed for ACG 154 from the subsp. hypogaea var. hypogaea and ACG 107 from the subsp. fastigiata var. vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The 100-seed weight was the highest in genotype Golden. Indeed, the seed size of Golden genotype is bold as compared with other genotypes (Naeem-ud-Din et al, 2009;Yol and Uzun, 2018) which eventually enhanced the 100-seed weight in this study.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The 100-seed weight was the highest in genotype Golden. Indeed, the seed size of Golden genotype is bold as compared with other genotypes (Naeem-ud-Din et al, 2009;Yol and Uzun, 2018) which eventually enhanced the 100-seed weight in this study.…”
Section: Discussionmentioning
confidence: 51%
“…Peanut (Arachis hypogaea L.) is an important kharif oilseed crop which has an oil content of~50%, and its seeds also contain surplus quantities of iron and vitamins A and B (Prasad et al, 2010;Arioglu et al, 2018;Dragičević et al, 2018;Yol and Uzun, 2018). Now a day, peanut is cultivated in more than 40 countries including United States of America, China, Mayanmar, Argentina, India, Brazil, Pakistan, Sudan, Nigeria, Indonesia and Senegal being the top producers of peanut in the world.…”
Section: Introductionmentioning
confidence: 99%
“…hypogaea var. hypogaea) used in this study had this spontaneous mutation 52) which was frequent among subspecies hypogaea accessions 67) . A new mutation was therefore identified at position 861 causing glycine to aspartic acid transition in the present investigation.…”
Section: Discussionmentioning
confidence: 97%
“…hypogaea. It has good agronomic traits such as large pods, high yielding and shelling percentage 52) . The seeds of this cultivar were obtained from the West Mediterranean Agricultural Research Institute of Turkey.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Yol et al (2017) reported the oil content of peanut genetic materials as between 31.7 -57.0%, oleic acid contents as between 35.3 -60.9% and linoleic acid contents as between 16.1 -43.6%. Greater adaptation to certain environmental conditions may contribute to high seed yield and quality of peanuts (Yol and Uzun, 2018). Growing techniques greatly influence oil content and fatty acid composition.…”
Section: Introductionmentioning
confidence: 99%